2005
DOI: 10.1111/j.1365-2842.2005.01513.x
|View full text |Cite
|
Sign up to set email alerts
|

Home‐exercise regimes for the management of non‐specific temporomandibular disorders

Abstract: There is a consensus on treatment strategies for temporomandibular disorders (TMDs) being reversible. Among reversible therapies, physiotherapy is often chosen for the treatment of TMD pain and dysfunction because it is simple and non-invasive, it has a low cost as compared with other treatments, it allows an easy self-management approach, it allows a good doctor-patient communication, and it can be managed by the general practitioner. Home-exercises regime protocols are reviewed in this article in the context… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
111
0
20

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(133 citation statements)
references
References 26 publications
2
111
0
20
Order By: Relevance
“…In this context, physical therapy can be an effective resource in cases of TMD, especially for those in which the pain persists (28).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, physical therapy can be an effective resource in cases of TMD, especially for those in which the pain persists (28).…”
Section: Discussionmentioning
confidence: 99%
“…Exercises and education about correct performance of these exercises was more effi cient than splint therapy when focused on muscular pain relief in patients with TM disorders (15).…”
Section: Discussionmentioning
confidence: 99%
“…[13] Knežević have shown that conventional therapy is also useful in relieving trismus in patients with MPDS. [14][15][16] According to Al Quran et al reduction in mouth opening is related to spasm of closing muscles, which leads to trismus. Reduction in mouth opening further adds to the discomfort of the patient as he finds difficulty in food intake and mastication and it is desirable to bring about improvement in the trismus.…”
Section: Medicationmentioning
confidence: 99%